2016
DOI: 10.1159/000444385
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Fine Needle Aspiration of Orbital Lesions: A Case Series

Abstract: Objective: This paper analyzes a series of ultrasound (US)-guided orbital fine needle aspirations (FNAs) which provide diagnostic information that cytopathologists approaching orbital lesions for the first time can find useful and underlines the importance of teamwork. Study Design: The investigators retrospectively obtained data from 24 consecutive orbital FNAs. For all patients, a complete clinicoradiological database was created. FNAs were performed under US guidance with 25-gauge needles and an aspiration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 25 publications
0
10
0
1
Order By: Relevance
“…8 We present the complications following ultrasoundguided orbital sampling described in the literature found in our review in Table 1. [12][13][14] Cutaneous eyelid haematoma was the most commonly encountered complication following ultrasound-guided sampling. This represents a minor complication that is not expected to cause permanent damage and the incidence cannot be reduced with image guidance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…8 We present the complications following ultrasoundguided orbital sampling described in the literature found in our review in Table 1. [12][13][14] Cutaneous eyelid haematoma was the most commonly encountered complication following ultrasound-guided sampling. This represents a minor complication that is not expected to cause permanent damage and the incidence cannot be reduced with image guidance.…”
Section: Discussionmentioning
confidence: 99%
“…6 Moreover, there is a purported increased risk of tumour seeding secondary to core biopsy procedures again due to the larger calibre of the needle. 6,14 For these reasons, FNA is often used as the initial sampling procedure and, for many tumours, cytology is adequate to produce a diagnosis. A number of non-ophthalmological studies have shown that increased diagnostic accuracy can be achieved with core biopsy over FNA without increasing the number of complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For cases for which both cytology and histopathology results were available, the rate of disagreement between the two modalities was surprisingly high but similar to that reported in the physician‐based literature. In people, fine needle aspirate for cytology of orbital lesions is nondiagnostic in 10%‐30% of cases and discordant with later histopathology in 10%‐31% of cases, while in our patient population 15% of cytology samples were nondiagnostic and 17% were overturned by later histopathology . No specific causative factors could be identified for cases in which cytology samples were considered nondiagnostic or were initially characterized as representative of an inflammatory rather than neoplastic process.…”
Section: Discussionmentioning
confidence: 59%
“…In people, fine needle aspirate for cytology of orbital lesions is nondiagnostic in 10%-30% of cases and discordant with later histopathology in 10%-31% of cases, while in our patient population 15% of cytology samples were nondiagnostic and 17% were overturned by later histopathology. [22][23][24][25][26] No specific causative factors could be identified for cases in which cytology samples were considered nondiagnostic or were initially characterized as representative of an inflammatory rather than neoplastic process. Of the 11 samples in these categories, 10 came from dogs who had undergone a CT and eight were obtained using ultrasound guidance, suggesting that failure to sample the lesion of interest was unlikely to be the reason for discordance.…”
Section: Discussionmentioning
confidence: 99%